Groundwater characteristics and climate and ecological evolution in the Badain Jaran Desert in the southwest Mongolian Plateau - Zhe Wang; Li-juan Wang; Jian-mei Shen; Zhen-long Nie; Ling-qun Meng; Le Cao; Shi-bo Wei; Xiang-feng Zeng (China Geology, 2021)
The Badain Jaran Desert is the third largest desert in China, covering an area of 50000 km2. It lies in Northwest China, where the arid and rainless natural environment has a great impact on the climate, environment, and human living conditions. Based on the results of 1∶250000 regional hydrogeological surveys and previous researches, this study systematically investigates the circulation characteristics and resource properties of the groundwater as well as the evolution of the climate and ecological environment since the Quaternary in the Badain Jaran Desert by means of geophysical exploration, hydrogeological drilling, hydrogeochemistry, and isotopic tracing. The results are as follows. (1) The groundwater in the Badain Jaran Desert is mainly recharged through the infiltration of local precipitation and has poor renewability. The groundwater recharge in the desert was calculated to be 1.8684×108 m3/a using the water balance method. (2) The Badain Jaran Desert has experienced four humid stages since the Quaternary, namely MIS 13-15, MIS 5, MIS 3, and the Early–Middle Holocene, but the climate in the desert has shown a trend towards aridity overall. The average annual temperature in the Badain Jaran Desert has significantly increased in the past 50 years. In detail, it has increased by about 2.5°C, with a higher rate in the south than in the north. Meanwhile, the precipitation amount has shown high spatial variability and the climate has shown a warming-drying trend in the past 50 years. (3) The lakes in the hinterland of the Badain Jaran Desert continuously shrank during 1973–2015. However, the vegetation communities maintained a highly natural distribution during 2000–2016, with the vegetation cover has increased overall. Accordingly, the Badain Jaran Desert did not show any notable expansion in that period. This study deepens the understanding of groundwater circulation and the climate and ecological evolution in the Badain Jaran Desert. It will provide a scientific basis for the rational exploitation of the groundwater resources and the ecological protection and restoration in the Badain Jaran Desert.© 2021 China Geology Editorial Office.